Association of Acute Kidney Injury Receiving Kidney Replacement Therapy With Prognosis of Critically Ill Patients With and Without Cancer: A Retrospective Study. Issue 11 (November 2021) - Druml, Wilfred; Zajic, Paul; Schellongowski, Peter; Fellinger, Tobias; Metnitz, Barbara; Posch, Martin; Metnitz, Philipp G. H.
Abstract : OBJECTIVES: To assess outcomes of cancer patients receiving kidney replacement therapy due to acute kidney injury in ICUs and compare these with other patient groups receiving kidney replacement therapy in ICUs. DESIGN: Retrospective registry analysis. SETTING: Prospectively collected database of 296, 424 ICU patients. PATIENTS: Patients with and without solid cancer with acute kidney injury necessitating kidney replacement therapy were identified and compared with those without acute kidney injury necessitating kidney replacement therapy. INTERVENTIONS: Descriptive statistics were used to ascertain prevalence of acute kidney injury necessitating kidney replacement therapy and solid cancer in ICU patients. Association of acute kidney injury necessitating kidney replacement therapy and cancer with prognosis was assessed using logistic regression analysis. To compare the attributable mortality of acute kidney injury necessitating kidney replacement therapy, 20, 154 noncancer patients and 2, 411 cancer patients without acute kidney injury necessitating kidney replacement therapy were matched with 12, 827 noncancer patients and 1, 079 cancer patients with acute kidney injury necessitating kidney replacement therapy. MEASUREMENTS AND MAIN RESULTS: Thirty-five thousand three hundred fifty-six ICU patients (11.9%) had solid cancer. Acute kidney injury necessitating kidney replacement therapy was present in 1, 408 (4.0%) cancer patients and 13, 637 (5.2%) noncancer patients. Crude ICU and hospital mortality was higher in the cancer group (646 [45.9%] vs 4, 674 [34.3%], p < 0.001, and 787 [55.9%] vs 5, 935 [43.5%], p < 0.001). In multivariable logistic regression analyses, odds ratio (95% CI) for hospital mortality was 1.73 (1.62–1.85) for cancer compared with no cancer 3.57 (3.32–3.83) for acute kidney injury necessitating kidney replacement therapy and 1.07 (0.86–1.33) for their interaction. In the matched subcohort, attributable hospital mortality of acute kidney injury necessitating kidney replacement therapy was 56.7% in noncancer patients and 48.0% in cancer patients. CONCLUSIONS: Occurrence rate of acute kidney injury necessitating kidney replacement therapy and prognosis in ICU patients with solid cancer are comparable with other ICU patient groups. In cancer, acute kidney injury necessitating kidney replacement therapy is associated with higher crude hospital mortality. However, the specific attributable mortality conveyed by acute kidney injury necessitating kidney replacement therapy is actually lower in cancer patients than in noncancer patients. Diagnosis of cancer per se does not justify withholding kidney replacement therapy. Abstract : Supplemental Digital Content is available in the text.